AUTOMATIC WHEEL CHAIRS WITH ERGONOMIC DESIGN AS ALTERNATIVE SUPPORT THERAPY STROKE PATIENT - Arda Widyatama; Syukri Ainun Alfath; Juwono Ardiansah; Agung Prijo Budijono (AIBPM Publisher, 2018)
The purpose The purpose of this study is to create a hybrid electric wheelchair that can be driven electrically and manually as a therapy of stroke patients to perform activities independently. Method The method used to produce wheelchair in this study is QFD (Quality Function Deployment). It is made based on the conditions and desires of patients with stroke. Voice of Customer (VOC) of them becomes an input in making Ergonomic Wheelchair with Easy to Use, Hybrid, Flexible and Knockdown. Results, The results show that the hybrid’s can help stroke patients because it is designed based on human body size or anthropometry in Indonesia and based on ISO 7176-5 standard. The driver used is a 12V DC wiper motor, controlled by a BLDC controller. The Findings The findings of this study are the hybrid’s drives that can be electrically driven and manual. It is designed based on human body size or anthropometry in Indonesia and based on ISO 7176-5 standard. Keywords : Automatic Wheelchair, Patient Stroke Therapy Equipment, Ergonomic Wheelchair